Impacts and response strategies of the COVID-19 pandemic on the construction industry using structural equation modeling - Kassem, Mukhtar A.; Afiqah R., Radzi; Pradeep, Asankha; Algahtany, Mohammed; Abdul Rahimi, Abdul Rahman (MDPI, 2023)
The COVID-19 pandemic is one of the most serious global health crises. It has had a massive impact on the global workforce and workplaces, causing enormous changes in the working environment and raising concerns among organizations. Due to the pandemic, the construction industry has faced more challenges in delivering projects on time and within budget. This study aims to determine the relationship between the impacts and response strategies of COVID-19 in Sri Lankan construction projects. A systematic literature review and semi-structured interviews with industry professionals identified twelve COVID-19 impacts and twenty-two response strategies needed to mitigate the impacts. A structured questionnaire survey was then conducted with Sri Lankan construction professionals. The gathered data were analyzed using the Kruskal–Wallis test, exploratory factor analysis (EFA), and partial least-squares structural equation modeling (PLS-SEM). A model and six hypotheses were developed to explain the impact and strategy. The results revealed that it is necessary to focus on the impacts related to the project, develop the necessary strategies from a financial point of view, and supply the necessary materials and equipment. During COVID-19, organizational management and information exchange should be enhanced, along with a project’s workforce and its provision. The study findings could aid industry professionals and policymakers in comprehending the pandemic and developing strategies to mitigate the effects of COVID-19 on Sri Lankan construction projects.